Eliminating export subsidies for inclusive trade - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
IFPRI’s trade research has been contributing to discussions on trade policies and rules at the World Trade Organization (WTO). Recent discussions, debates, and final resolution around the important issue of eliminating agricultural export subsidies were informed by IFPRI’s research: Catastrophic flood or inoffensive drizzle: Assessing the impact of countries using the existing water in export subsidies (2015), Export Subsidies and Export Credits (2014), and That Was Then But This Is Now: Multifunctionality In Industry And Agriculture (2002), which have been widely disseminated among WTO member countries. In December 2015 at WTO’s 10th Ministerial Conference in Nairobi, WTO member countries agreed that export subsidies for agriculture would be abolished.